(3ebJd GdMSjf Ydjg GdSdGes - (3dhW Hf jMji Hf SYjO Hf eNfa GdCROj GdZGeOj, CHh eNfa,J (B157 (3g` s
(3ChdgG (B:s
(3MOKfG CHh eNfa Yf GdCTYK s
(3BNQgG (B:s
(3CMH eMH Bd eMeO eG CMHge JeJ GdSjQI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B245 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B157s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B213 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B289 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdCeHQhRjGfG (B(233f) s
Keywords: (3GdJGQjNs